Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry (MALDI-TOF MS) Applications in Bacteriology: brazilian contributions - Pellegrino, Flávia Lúcia Piffano Costa; Chagas, Thiago Pavoni Gomes; Alves, Maria Silvana; Carvalho-Assef, Ana Paula D’Alincourt; Chapeaurouge, Alexander; Asensi, Marise Dutra (HU Revista, 2018)
Among its innumerous applications in Bacteriology, the Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry (MALDI-TOF MS) technique is evolving as a powerful tool for bacterial identification and antimicrobial resistance investigation. Publications have evaluated the MALDI-TOF MS performance in the identification of a series of bacterial pathogens, including the most common severe infectious agents, emergent pathogens involved with outbreaks of healthcare-associated infections, rare pathogens, and those whose isolation in culture media is difficult. As compared to conventional methods of bacterial identification, MALDI-TOF MS has proven to be a fast, accurate and cost-effective technique. Currently, MALDI-TOF MS has been used in antimicrobial resistance studies, since it has shown to be an efficient tool in detecting specific resistance mechanisms in bacteria, such as beta-lactamases production, for example. Here, we describe the advances in this growing field of mass spectrometry applied to Bacteriology, including Brazilian contributions.